PC.21 Eye-tracking methodology for the assessment of social function in infancy. (9th June 2014) - Gillespie-Smith, K; Boardman, JP; Murray, I; Norman, J; O'Hare, A; Fletcher-Watson, S
Abstract : Background: Eye-tracking has provided new insights into the development of infant cognition and is currently being explored as a potential way to identify early biomarkers of later difficulty. We aimed to assess social cognitive ability across levels of stimulus complexity in infancy. Methods: Participants were 32 typically-developing (TD) infants aged 6–12 months, recruited with ethical approval (from University of Edinburgh). We measured 3 aspects of social cognition using stimuli of increasing complexity: attention distributed across faces; attention to faces in a grid-like array; and attention to faces embedded in naturalistic scenes. Results: In each task we found evidence of longer fixation duration on socially informative content compared with other regions (i.e. eyes versus mouths, faces versus other objects; Wilcoxon signed-ranks all p Conclusions: Each task showed evidence of infant interest in social information. Evidence from first fixation data reveals that these social preferences are mediated by stimulus complexity. Caution must therefore be taken when examining early biomarkers in social cognition because stimulus complexity may influence infants' capacity to demonstrate social attentional preferences. These findings have implications for development of eye-tracking tasks as biomarkers of later difficulty.